Construction of frailty and risk prediction models in maintenance hemodialysis patients: a cross-sectional study - Liu, Huan; Tao, Mingfen; Zhang, Man; Zhou, Zhiqing; Ni, Yang; Wang, Qin; Zhang, Xiang; Chi, Chenru; Yang, Dan; Chen, Mengqi; Tao, Xiubin; Zhang, Ming (Frontiers in Medicine, 2024)
As the prevalence of diabetic nephropathy and hypertensive nephropathy increases with age in mainland China, the number of patients with end-stage renal disease is increasing, leading to an increase in the number of patients receiving maintenance hemodialysis.Considering the harmful effects of frailty on the health of maintenance hemodialysis patients, this study aims to identify hemodialysis patients at risk for frailty at an early stage, in order to prevent or delay the progression of frailty in the early stage, so as to prevent the adverse consequences of frailty.A total of 479 patients admitted to the the blood purification centers of two grade tertiary hospitals in Anhui Province, China, using convenient sampling. The Frailty Scale, the SARC-F questionnaire, the Simplified Food Appetite Questionnaire (SNAQ) and the mini nutritional assessment short-form (MNA-SF) were used in the study. Pearson correlation analysis was used to explore the correlation among the frailty influencing factors.The incidence of frailty was 24.0% among 479 Chinese haemodialysis patients. Gender(P<0.05), Malnutrition(P<0.001), sarcopenia (P<0.001), and feel tired after dialysis(P<0.001) were highly correlated with frailty in Chinese haemodialysis patients. Serum albumin concentration(P<0.05) was a protective factor of frailty.This survey shows that frailty was highly prevalent among Chinese haemodialysis patients. Medical staff and their families should make early judgments and carry out interventions on the risk of frailty.